INTERVENÇÃO PEDAGÓGICA À LUZ DA ABORDAGEM COGNITIVISTA PARA ENSINO DE EDUCAÇÃO FINANCEIRA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
Financial education is a subject that still presents great challenges for its dissemination in Brazil since, despite the efforts made in recent years, it still lacks studies, especially regarding methodological discussions and teaching practices. This study sought to describe a pedagogical intervention in financial education from the cognitive approach, in a project carried out in the counter shift of the academic period of a public educational institution. It is a descriptive research of qualitative nature and had as an analysis procedure the observation carried out by the mediators, from the data collected through questionnaires filled out by the students. Students from technical courses integrated to high school at a Federal Educational Institution participated in the research and had as mediators a Finance Professor and a Psychologist. As a result, the cognitive approach was positive for the realization of financial education initiatives, since the fact that the teacher presents himself as a mediator and the student as an active part in the learning process enabled the redefinition of the school space, the course and the contents studied.
Keywords: Cognitive Approach; Financial Education; Pedagogical Practice; Teenager